Entrepreneurship in the museum: advantages, obstacles, solutions - Leila Mirghadr; Elahe Kazemi; Seyed Saeed Hashemi (اقتصاد شهری, 2025)
Today, considering the vital role of museums in society, discovery and search for entrepreneurship in the museum is one of the motivations of researchers in the field of museum studies and management, as well as tourism which can, in addition to preserving and presenting better the heritage and collections of the museum, provide opportunities for improving the economic situation, diversifying the tourism market, creating a unique experience, educating and learning visitors, and a suitable platform for discussing and expressing political and social problems and culture. Entrepreneurship in museums, along with its advantages, obstacles, and potential solutions, has not been extensively studied in the context of Iranian museums. The current research pursues the following three goals: 1) Identifying the advantages of entrepreneurship in the museum, 2) Identifying the barriers to the development of entrepreneurship in the museum context, and 3) Identifying the appropriate solutions and strategies for the development of entrepreneurship in the museum. This research is exploratory research and qualitative method (thematic analysis) is used. The statistical community of the research was formed by experts in the fields of entrepreneurship, tourism, and museums, and the data analysis tool is MaxqDA software. The findings of the research indicate that the museum has the necessary potential for the development of entrepreneurship. Furthermore, cultural and social entrepreneurship, tourism with an entrepreneurial perspective, educational opportunities as entrepreneurship advantages, and structural, environmental, and behavioral factors were identified as entrepreneurship obstacles in the museum. In the end, the 6 strategies of market penetration, product development, collaboration, policy making, education, and cultural awareness were introduced as suitable strategies for entrepreneurship in the museum.